Optimization via simulation of catchment basin management using a discrete-event approach. (January 2015) - Santucci, J F; Capocchi, L
This paper deals with discrete-event simulation-based optimization of a catchment basin management. The integration of optimization techniques into modeling and simulation relies on the evolution of the studied model using decisions based on previous simulation results. Three different categories of optimization via simulation methods can be found in the literature: ranking-and-selection methods, discrete and continuous optimization via simulation methods. In this paper, we explain how an iterative process allows us to integrate continuous optimization via simulation algorithms into a discrete-event simulation in order to optimize the management of a catchment basin. We have performed a comparison between optimization methods belonging to the three categories of optimization via simulation methods when they are applied to the management of a catchment basin. An analysis of the comparison allows us to point out the benefits of continuous optimization via simulation methods compared with rank-and-selection and discrete optimization via simulation methods in the case of the optimization of a catchment basin management.